Implementing innovation: a stakeholder competency-based approach for BIM. Issue 4 (30th September 2014) - Pour Rahimian, Farzad; Ibrahim, Rahinah; Murphy, M.E.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of the paper was twofold: to review established literature to define and classify BIM; and to identify gaps in current BIM literature with respect to stakeholder competency. Construction projects adopt innovation to address client requirements. Building information modelling (BIM) has been cited as one such innovation. However there is concern that the industry lacks the mechanisms to effectively implement BIM. It is proposed that the problem lies in that BIM is currently being delivered as a project rather than an innovation; and the failure to address stakeholder competency as the key delivery agent of BIM. Design/methodology/approach – A qualitative study using literature and gap analysis techniques was undertaken to establish the "state of the art". Using an established Competency Framework 31, studies on BIM were assessed. A matrix was developed aligning the BIM studies with the Competency Framework and the findings systematically evaluated to identify gaps in the current literature. Findings – BIM was defined as a technical innovation and classified as a "System" of multiple innovations. Aligning the literature identified that BIM literature has largely focussed on strategic competence with some evidence of technical competence. However, there was scant investigation of information and communication competence which ranks as the most critical competency for BIM implementation. The study identified that whilst the competency-related literature on BIM was not yet rich enough to provide a sound conceptual foundation for investigation, it was evident that BIM implementation aligns closely with the innovation process. Practical implications – The findings highlighted the imperative of developing a competency-based approach for BIM implementation. Social implications – It was anticipated that a competency-based approach will provide insights to benefit construction industry clients and inform the targeted training of project stakeholders. Originality/value – BIM must be implemented as an innovation using a competency-based management approach as the key delivery mechanism.